The Effect of @englishhero TikTok Video on Students' Vocabulary Mastery at the 10th grade of MA Zainul Hasan Pare - ST. Dewi Fatimatuz Zahro; Muhammad Yasminto (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
This study aims to know the effect of @englishhero TikTok Video on Students' Vocabulary Mastery at the 10th Grade of MA Zainul Hasan Pare through pre experimental research design conducted with only pre-test post-test one experimental group. The researchers took 24 students as the sample of the study from 65 population by using simple random sampling. To collect the data, the researchers used vocabulary written test with 25 items in essay format. In analyzing the data, the researcherss used IBM SPSS statistic versions. 20 application of non-parametric t.test from Wilcoxon test, because data was not normally distributed. It aims to know whether there is or not a difference between before given the treatment and after given the treatment using @englishhero TikTok Video on Students' Vocabulary Mastery. After collecting and calculating data, the researchers found that mean score of post-test 95.33 was higher than pre-test 63.50. In testing the hypothesis, they used t-test formula. The researchers found that p value (Asymp. Sig. (2-tailed)) =0.000 < 0.05, at the level significance of df = 23. So, the null hypothesis was rejected. It means that @englishhero TikTok Video affects Students' Vocabulary Mastery at the 10th Grade of MA Zainul Hasan Pare.